Interferon-gamma 1b-induced gene expression alters neutrophil function in patients with chronic granulomatous disease - Daniel R. Ambruso; Natalie J. Briones; Alexander D. Tran; Bridget Sanford; Christine Childs; Ben Z. Katz; Michael Ellison; Richard B. Johnston; Kenneth L. Jones (PLoS ONE, 2025)
Interferon-gamma (IFN-γ) decreases infections in chronic granulomatous disease (CGD) with variably incomplete restoration of the fundamental CGD defect, converting oxygen to microbicidal oxidants during phagocytosis. We sought to understand other IFN-γ effects that could contribute to protection of CGD patients. We measured neutrophil function, gene expression, and biochemical parameters in nine CGD patients off IFN-γ and 10–12 hours after the first (1st) and fourth (4th) IFN-γ injection. Non-directed motility and bactericidal activity increased after IFN-γ administration; ingestion remained unchanged. Stimulated release of superoxide anion (O2-) was minimally changed. Treatment decreased expression of 483 genes and increased 386. Expression of eleven genes associated with neutrophil activity was upregulated. Genes not routinely associated with neutrophil function also demonstrated increased expression, including MHCI & II proteins, guanylate-binding proteins, and an enzyme synthesizing a nitric-oxide (NO) synthetase cofactor. CD11b expression, F-actin assembly, and CD 274 antigen were increased after treatment as was NO in neutrophil lysates. Formation of neutrophil extracellular traps after ingestion of staphylococci was increased off IFN-γ compared with controls but moved toward normal after IFN-γ administration. IFN-γ protects against infection in CGD by several mechanisms that could potentially support others with compromised host defense. Trial registration ClinicalTrials.gov NCT03548818